UMP: anti-hysteria kit works - T. N., Alagesh; Zafira, Anwar (Penerbit, Percetakan New Straits Times, 2015)
Universiti Malaysia Pahang (UMP) has defended its "anti-hysteria kit", which has been ridiculed by netizens and some politicians